2017
DOI: 10.1136/archdischild-2017-312826
|View full text |Cite
|
Sign up to set email alerts
|

Fine particulate pollution and asthma exacerbations

Abstract: We found an association between daily asthma exacerbation in paediatric visits to the ED and fine particulate air pollutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
61
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 13 publications
2
61
1
Order By: Relevance
“…26 Also, a study by Bouazza et al, on children, in Paris, showed that there was a significant relation between exposure to air pollution especially particulate matter (PM) and exacerbations of asthma symptoms in children visiting the emergency department. 27 Another study by Salimi et al, about long-term exposure to air pollution and hospitalization for respiratory diseases in Australia, showed that there was a weak but direct relation between exposure to air pollution and hospitalization for asthma. 28 According to the American College of Lung Physicians (CHEST) report in 2018, 65 million people suffer from chronic obstructive pulmonary disease (COPD) and 3 million die each year, making it the third leading cause of death worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…26 Also, a study by Bouazza et al, on children, in Paris, showed that there was a significant relation between exposure to air pollution especially particulate matter (PM) and exacerbations of asthma symptoms in children visiting the emergency department. 27 Another study by Salimi et al, about long-term exposure to air pollution and hospitalization for respiratory diseases in Australia, showed that there was a weak but direct relation between exposure to air pollution and hospitalization for asthma. 28 According to the American College of Lung Physicians (CHEST) report in 2018, 65 million people suffer from chronic obstructive pulmonary disease (COPD) and 3 million die each year, making it the third leading cause of death worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Bouazza et al 3 did not detect additional effects of O 3 or NO 2 on asthma ED visits after accounting for PM 2.5 , which suggests that fine particles could be the trigger of asthma exacerbations on days of relatively high air pollution. However, PM 2.5 and NO 2 correlated strongly and could be surrogates of traffic-related pollution in urban areas.…”
mentioning
confidence: 95%
“…In a large longitudinal study presented in this journal, Bouazza et al 3 examined paediatric visits for asthma exacerbation to emergency departments (EDs) in Paris, France, in relation to air pollution and other factors such as daily weather (including temperature and humidity), viral infections and pollen data. The authors analysed over 47 000 cases of paediatric visits in 20 hospitals over 5 years using a non-linear modelling approach to examine the exposure–response relationship between single or multiple pollutants and asthma exacerbations.…”
mentioning
confidence: 99%
See 2 more Smart Citations